2017
DOI: 10.1038/srep40395
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-functionalized mesoporous onion-like silica as a new matrix for immobilization of lipase Candida sp. 99-125

Abstract: Dopmine functionalized mesoporous onion-like silica (DPMS) was synthesized via a biomimetic coating, and lipase Candida sp. 99-125 (LCS) was immobilized in DPMS (LCS@DPMS) by physical adsorption in this study. The DPMS was characterized by SEM, TEM, BET and FT-IR, and it was shown that the DPMS had clear multishell structures with large surface area of 419 m2/g. The activity, pH stability, thermal stability, storage stability, and reusability of the LCS@DPMS were investigated in detail. The stabilities of LCS@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…32 After modification with dopamine, poly- Figure 5C and 5D, new chemical bonds of C═O (287.1 eV) and C═C (284.2 eV) could be found in Figure 5D, which represented the C 1s of poly-dopamine on the surface of DPMS. Furthermore, the three sources of the N element were -NH (399.7 eV), -NH 2 (401.6 eV), and -N = (398.9 eV), 26,27 which indicated that dopamine attached onto SBA-15 successfully. 33 According to Figure 5F, the N element could be detected easily in DPMS.…”
Section: Structural Evolution Of Sba-15 and Dpmsmentioning
confidence: 95%
See 3 more Smart Citations
“…32 After modification with dopamine, poly- Figure 5C and 5D, new chemical bonds of C═O (287.1 eV) and C═C (284.2 eV) could be found in Figure 5D, which represented the C 1s of poly-dopamine on the surface of DPMS. Furthermore, the three sources of the N element were -NH (399.7 eV), -NH 2 (401.6 eV), and -N = (398.9 eV), 26,27 which indicated that dopamine attached onto SBA-15 successfully. 33 According to Figure 5F, the N element could be detected easily in DPMS.…”
Section: Structural Evolution Of Sba-15 and Dpmsmentioning
confidence: 95%
“…33 According to Figure 5F, the N element could be detected easily in DPMS. Furthermore, the three sources of the N element were -NH (399.7 eV), -NH 2 (401.6 eV), and -N = (398.9 eV), 26,27 which indicated that dopamine attached onto SBA-15 successfully. Figure 6 exhibits the XPS test curves of DPMS and SBA-15.…”
Section: Structural Evolution Of Sba-15 and Dpmsmentioning
confidence: 95%
See 2 more Smart Citations
“…56 Lipase generally shows a severe decrease in catalytic activity after immobilization which rises from the increased mass-transfer limitations between the enzyme and substrate, the fractional blocking of enzyme active sites or alternation of native enzyme structure during the immobilization process. [110][111][112][113] Interfacial activation concept has developed as an elegant approach to enhance the activity of immobilized lipase over the recent years. 114 It has been well-documented that the lipase molecule possesses a flexible configuration in which the active site is covered by a hydrophobic and movable region of the lipase molecule, called the "lid".…”
Section: Interfacial Activationmentioning
confidence: 99%